Thermodynamic Evaluations of the Al-Li-Cu-Mg-Zr Systems - Marko Hämäläinen (1998)
The investigation of the AlLiCuMgZr system is accomplished in this report. The evaluations of the CuMgZr and CuLiMg systems and the experimental study of the AlLiCuMg system were carried out during the COST 507 second round. The evaluation of the CuLiMg system was based on the DSC experiments at the large range of composition. The parameters of the excess Gibbs energy obtained agreed quite well with the temperatures of the phase transformations but the fit was not so good using the experimental enthalpies. The decomposition temperature of the phase was fixed at 702.7 and was not defined earlier in the literature. The optimisation of the CuMgZr system was based on the experimental data from the literature and on one set of the DTA experiments measured. The calculated phase diagram was in good agreement with the data used. The existence of the new phase as well as the parameters of formation of the excess Gibbs energy contributed well the system studied. The phase relations near to Alrich corner containing up to 7 wt.% Li, 7 wt.% Mg and 10 wt.% Cu were investigated using microscopy analysis, quality local Xray spectral analysis and Xray phase analysis in the experimental study of the AlLiCuMg system done by Baikov Institute of Metallurgy.